MODERN VIEW OF THE ISSUE OF USING LIFESTYLE AS A MEANS OF NON-DRUG THERAPY OF METABOLIC SYNDROME - Kalmykova, Yu. S. (Rehabilitation and Recreation, 2023)
The aim of the article is to analyse scientific resources devoted to the study of modern views on a healthy lifestyle for people with metabolic syndrome. Research methods. Analytical and bibliosemantic methods were used. A review and analysis of current domestic and foreign literature sources devoted to non-drug therapy of metabolic syndrome was conducted. The results. Metabolic syndrome remains the most important problem of society related to early and high disability, premature aging and mortality. It is important that metabolic syndrome is a reversible condition in case of appropriate timely treatment. Changing the lifestyle is one of the most important approaches to treatment of metabolic syndrome, which includes correction of excess weight, increased physical activity, etc. Increasing physical activity plays a significant role in eliminating the consequences of metabolic syndrome. Physical activity increases the oxidative processes in muscles, and therefore, carbohydrates and fatty acids usage is also enhanced. Physical activity promotes the use of intramuscular triglycerides and free fatty acids as energy material, reducing insulin resistance. Physical activity is the most important measure for controlling body weight. Even in the absence of weight loss, physical activity is associated with many beneficial effects, such as improving the functional state of the cardiovascular system and possibly reducing insulin resistance. Experts believe that it is dynamic training that causes more significant increase in functional capabilities of circulatory system, and that an optimal option for using physical exercises is a combination of static and dynamic physical loads. Aerobic physical load increases tissue sensitivity to insulin, and it must be taken into account that dynamic load is quite difficult for obese people. Physical exercises are performed at an average pace, with the maximum amplitude, however, taking into account the physical capabilities of the patient. In addition, clinical studies of the Diabetes Prevention Program indicate that physical activity in patients with insulin resistance, as well as their diet and lifestyle change all reduce the number of new cases of T2DM more effectively than the use of drug therapy. Conclusions. The spread of metabolic syndrome has become epidemic in Ukraine. One of the most important components of metabolic syndrome pathogenesis is abdominal obesity. Specialists pay considerable attention to reducing body weight due to lifestyle, namely physical activity, eating habits, and giving up bad habits.